Frontal QRS–T angle remains unchanged in fibromyalgia: a cross-sectional study with implications for routine ECG screening - Tezcan, Hüseyin; Tezcan, Ezgi Akyıldız (Frontiers in Medicine, 2025)
AimFibromyalgia syndrome (FMS) is a chronic condition characterized by widespread pain and associated with systemic diseases. Although autonomic dysfunction in FMS may predispose to cardiac arrhythmias, its impact on cardiac parameters, such as the frontal QRS-T [f(QRS-T)] angle, remains unclear. This study aimed to investigate the f(QRS-T) angle in FMS patients compared to healthy controls.MethodsA total of 75 FMS patients and 75 healthy controls were included in this cross-sectional study. Disease severity was assessed using the Fibromyalgia Impact Questionnaire (FIQ). The f(QRS-T) angle was calculated from 12-lead electrocardiograms by a blinded cardiologist. Associations between the f(QRS-T) angle, FIQ scores, and duloxetine use were analyzed using appropriate statistical methods.ResultsNo significant differences in the f(QRS-T) angle were observed between FMS patients and controls (p = 0.973). Additionally, no correlation was found between FIQ scores and the f(QRS-T) angle (p = 0.725). Subgroup analysis revealed no significant differences in the f(QRS-T) angle between FMS patients using duloxetine and those not using it (p = 0.503).ConclusionContrary to concerns about subclinical cardiac involvement in FMS, our findings reveal no significant alterations in the f(QRS-T) angle among FMS patients. Moreover, disease severity and duloxetine use do not influence this parameter. These results challenge the assumption of clinically relevant cardiac dysregulation in FMS and suggest that routine ECG screening may not be necessary for patients with FMS. Nonetheless, longitudinal studies are warranted to fully clarify the long-term cardiac risk in this population.